The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1136/gut.2004.041616
|View full text |Cite
|
Sign up to set email alerts
|

Cost of illness of inflammatory bowel disease in the UK: a single centre retrospective study

Abstract: Background and aims: The potentially high costs of care associated with inflammatory bowel disease (IBD) are recognised but we have little knowledge of the scale, profile, or determinants of these costs in the UK. This study aimed to describe costs of illness for a group of IBD patients and determine factors associated with increased healthcare costs. Setting: A university hospital serving a target population of approximately 330 000. Patients and methods: A six month cohort of IBD patients receiving any form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
244
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(273 citation statements)
references
References 25 publications
18
244
0
3
Order By: Relevance
“…Crohn's disease is also very important for both the people suffering from the severe chronical illness with all its painful and difficult attributes and for the huge expenditure for treatment and additional costs (Juan et al, 2003;Bassi et al, 2004;Ebinger et al, 2004). Information already available is sufficient to accept the possibility of a risk for consumers resulting not only from the viable MAP, but also from inactive or dead cells and even from their structural components.…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease is also very important for both the people suffering from the severe chronical illness with all its painful and difficult attributes and for the huge expenditure for treatment and additional costs (Juan et al, 2003;Bassi et al, 2004;Ebinger et al, 2004). Information already available is sufficient to accept the possibility of a risk for consumers resulting not only from the viable MAP, but also from inactive or dead cells and even from their structural components.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of UC for the NHS is substantial, particularly in patients with poor disease control. Compared with quiescent IBD, disease relapse is associated with an estimated 2-3-fold increase in costs for non-hospitalised cases and a 20-fold increase in costs for hospitalised cases [3]. Approximately 80% patients with UC have mild-to-moderate disease, and approximately 20% have severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…24 Another study found that, over a 10-year period, the cost of hospitalization was 45% of the total cost of UC treatment. 25 Also, data from the Healthcare Cost and Utilization Project (HCUP) showed that the mean length of stay and the mean cost of hospitalization for inflammatory bowel diseases, including UC, were higher than for all conditions combined, using pooled data (6.1 days vs. 4.6 days and $9,200 vs. $7,700, respectively).…”
mentioning
confidence: 99%